The A-Z of the PhD Trajectory A Practical Guide for a Successful Journey - Lantsoght, Eva O. L. (Springer Texts in Education,, 2018)
This textbook is a guide to success during the PhD trajectory. The first part of this book takes the reader through all steps of the PhD trajectory, and the second part contains a unique glossary of terms and explanation relevant for PhD candidates. Written in the accessible language of the PhD Talk blogs, the book contains a great deal of practical advice for carrying out research, and presenting one's work. It includes tips and advice from current and former PhD candidates, thus representing a broad range of opinions. The book includes exercises that help PhD candidates get their work kick-started. It covers all steps of a doctoral journey in STEM: getting started in a program, planning the work, the literature review, the research question, experimental work, writing, presenting, online tools, presenting at one's first conference, writing the first journal paper, writing and defending the thesis, and the career after the PhD. Since a PhD trajectory is a deeply personal journey, this book suggests methods PhD candidates can try out, and teaches them how to figure out for themselves which proposed methods work for them, and how to find their own way of doing things.